Synthesis and characterization of carbon nanotubes in a vertical floating catalyst chemical vapour deposition reactor - Ahmed, Thamer H. (2011)
New approaches to synthesize randomly oriented MWNTs have been achieved in a vertical floating catalyst reactor. This approach based on the direct injection of the catalyst into the reactor in powder form by using a new catalyst delivery system. The catalyst was injected from the top of the reactor and simultaneously vaporized in the reactor, therefore,eliminating the need to have a traditional preheating of the catalyst. The ethylene gas as the reactant was used to push the catalyst powder into the reactor. The new catalyst delivery system consists of three main parts. The first part is a small chamber used as a temporary container for catalyst powder and having a conical bottom end to facilitate the flow of the powder (catalyst). The top end of the chamber is a removable cover equipped with inlet gas probe. Below the chamber, there is a control valve used to control the flow of catalyst into the reactor. This valve connected to a long thin tube (5 mm ID, 6 mm OD and L=460 mm) which could be inserted into the reactor at adjustable length. This arrangement is effective to increase the residence time and provide sufficient contact between the carbon source gas and the catalyst. Ferrocene was used as the catalyst precursor and ethylene as the carbon source. The experiments were performed at atmospheric pressure with process temperatures ranged between 650 ºC and 850 ºC under argon atmospheres. Argon was flown with flow rate of 650 ml/min through the system before the reaction to purge air from the reactor. Hydrogen and argon both are entering the reactor from the bottom. Layer of carbon nanotubes was grown on the reactor walls. The as-grown CNTs were characterized by Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM),High Resolution Transmission Electron Microscope (HRTEM) and Thermal Gravimetric Analysis (TGA). A parametric study was made to evaluate the influence of the most crucial experimental conditions on the growth of carbon nanotubes. Reaction temperature, catalyst weight, ethylene flow rate and reaction time were systematically varied and their influence on yield, purity, and diameter distribution of carbon nanotubes were evaluated. Although hydrogen and argon may affect the properties of CNTs, it requires an entirely different scope of study. A strong effect of the reaction temperature was found on nanotube growth. Five reaction temperatures from 650 ºC to 850 ºC were used. Both quality and quantity of CNTs synthesized were increased with the increase in synthesis temperature from 650 ºC to 750 ºC. Relatively, the highest purity and yield of CNTs deposit was obtained when reaction temperature was set at 750 ºC. Catalyst weight strongly influenced the formation of CNTs, the appropriate catalyst weight for growing CNTs with best yield and high purity among six weights (50,100,150,200,250 and 300 mg) used was 250 mg. High catalyst content form large clusters with low activity. Ethylene was found to play important roles in the production of CNTs, six different flow rates from 50 ml/min to 300 ml/min each 50 ml/min were used to investigate effect of ethylene on the yield, purity, diameter distribution and growth of carbon nanotubes. The optimal ethylene flow rate was 100 ml/min. The effect of the reaction time on the purity and yield of carbon nanotubes was studied from 15 minute to 90 minutes. The maximum yield of carbon nanotubes was achieved at 30 minutes, for reaction duration longer than 30 min the growth rate was continuously suppressed and gradually the catalyst loses its activity. There was no effect of the reaction time on the average diameter. The CNTs diameters increase with increasing these parameters under all experimental conditions. The optimum reaction have been achieved at the above conditions and the CNTs produced have yield of 148.4 wt%, purity of 89.4% and diameters from 8-53 nm. Structure and kinetic of produced carbon nanotubes were studied using HRTEM. The CNTs display a MWNTs structure of successive graphite sheets with hollow inside. Kinetics of MWNTs quantitatively described, the activation energy and frequency factor are calculated. The equation that fit the growth of carbon nanotubes was presented.